PENGELOLAAN SAMPAH DARI LINGKUNGAN TERKECIL DI KELURAHAN KASTURIAN KOTA TERNATE - Sahidun, Nurfitri; Haryati, Haryati (Institut Agama Islam Negeri Ternate, 2023)
The focus of this community service activity is to make various kinds of creativity from managing plastic waste at home specifically for the community, especially the women of Kasturian Village in Ternate City, North Maluku. This community service activity was carried out for one day, on the 13 of February 2023. The results of initial observations on this service partner found that there was still a lot of plastic waste donated by residents of the Kasturian sub-district in every existing trash can. Therefore, the service team provides counseling and at the same time practices managing waste from the smallest environment by making various kinds of creativity. The results obtained after this service are increasing the enthusiasm of the community to manage plastic waste into various kinds of creativity.Keywords: Plastic waste; Smallest Environment